Concern and counter-concern: The challenge of fragmented fears for the reguation of hydraulic fracturing. Issue 3 (July 2017) - Pearson, John; Lynch-Wood, Gary
Highlights: Hydraulic fracturing (fracking) is being tested in the United Kingdom as a means of accessing natural gas reserves. The current regulatory process proposed for this industry is complex and adapted from that for existing oil and gas projects. Local planning authorities, at present, hold considerable influence in the approval of hydraulic fracturing projects. Concerns over the process are bifurcated between civic and scientific groups. Future regulation might be influence by misguided concerns and as such neglect those supported by evidence. Abstract: Proposals to use the process of hydraulic fracturing (fracking) to extract natural gas in the United Kingdom has been met with both opposition and support as has often been the case for new extractive industries exploring new techniques or applications thereof. An idiosyncratic feature of the debate surrounding hydraulic fracturing is however the seeming lack of congruence of the concerns raised by experts and civic opposition. The authors consider the potential implications of this fragmentation of fears surrounding the process for its future regulation.